Evaluasi Media Pembelajaran Augmented Reality Bangun Datar/Ruang dengan Pendekatan Etnomatematika Rumah Adat Lengkong dalam Meningkatkan Kemampuan Spasial Siswa Sekolah Dasar - Anggraini, Cicilia Clara Devi; Wiradharma, Gunawan; Prasetyo, Mario Aditya; Anam, Khaerul (JOEAI (Journal of Education and Instruction), 2024)
Mathematics learning at the school level really needs to be linked to local culture by being incorporated into mathematics learning media to make it more contextual and interesting. This is known as the ethnomathematics approach. Previous research has produced augmented reality-based learning media applications for learning mathematics flat and spatial building materials using the cultural products of the lengkong traditional house from West Java. The product utilizes the latest technological developments that are used as learning media. This application is designed as a support in visualizing the learning of flat and space shapes materials at the elementary school (SD) level. A questionnaire was employed as the data collection procedure. Respondents of this study consisted of two parties, namely experts who were teaching staff (lecturers and teachers) and users who were PGSD students and students who used the application. The filled questionnaire measures the assessment which includes usefulness, ease of use, ease of learning, and user satisfaction. Data analysis in this research is quantitative descriptive. The learning application developed integrating augmented reality (AR) technology with an ethnomathematics approach showed significant results in improving the spatial abilities of elementary school students. AR technology allows a more real and interactive visualization of geometry objects, which is difficult to achieve through conventional learning methods. With this visualization, students can observe and interact with two- and three-dimensional building models so that their understanding of the structure and dynamics of spatial buildings increases. The ethnomathematics approach that connects mathematical concepts with local culture has made the subject matter more relevant to students' daily lives. This increases students' learning motivation as they can see firsthand the application of mathematical concepts in their cultural context.